The British empire : - Lynch, Michael (Hodder education, 2005)
Each title in the history category of Teach Yourself makes complex events accessible when you’re seeking an alternative to dry, academic texts. Incorporating gripping personal stories, our Teach Yourself History Books transform history from a record of facts and dates to a dynamic, fascinating experience.